The game of lives - Dashner, James, 1972- ([New York] : Delacorte Press, 2015)
The VirtNet has become a world of deadly consequences, and Kaine grows stronger by the day. If Kaine succeeds, it will mean worldwide cyber domination. And it looks like Michael and his friends are the only ones who can put the monster back in the box--if Michael can figure out who his friends really are.
Sequel to: The rule of thoughts.
730
Keywords: Computer games -- Fiction; Virtual reality -- Fiction; Cyberterrorism -- Fiction; Science fiction